The Effect of Motivation, Compensation, Work Environment on Work Performance Through Job Satisfaction PT XYZ Palm Oil Company - Wicaksono, Anang Bagus; Masyhuri; Suryantini, Any (School of Business, Bogor Agricultural University (SB-IPB), 2023)
PT XYZ Palm Oil Company faces problems related to the performance of harvest workers. This study aimed to determine the effect of Motivation, compensation, and work environment on work performance either directly or through job satisfaction at PT XYZ. Based on initial observations of Motivation, compensation, work environment, job satisfaction, and work performance, especially in oil palm harvest workers, showing a low level of Motivation, lack of appreciation given, and lack of satisfaction with the applicable compensation system, high workload, laziness at work, lack of expertise/skills, longer environmental adaptation and dissatisfaction with the applicable compensation system, so that the level of satisfaction and performance of PT XYZ is not optimal. This research design uses a quantitative descriptive method, and the population is 510 harvest workers, and the sample in this study amounted to 105 harvest worker respondents divided by proportional sampling. The data analysis method was carried out using SEM-PLS with the SmartPLS 3.0 application. The results showed that Motivation, compensation, and work environment positively and significantly affected work performance through job satisfaction. Based on the results of the study, it can be concluded that the level of influence of compensation is the most significant influence, followed by the influence of the work environment and work Motivation, so that the increasing level of job satisfaction, the higher the level of work performance of harvest workers. Keywords: work compensation, work motivation, palm oil, work environment, work performance